The first-aid advice and safety training (fast) parent programme to prevent unintentional home injuries in preschool children. (7th October 2012) - Mytton, J; Stewart-Brown, S; Hewison, C; Potter, B; Azuike, V; Park, P
Abstract : Background: Parenting programmes that improve understanding of the relationship between injury risk, parent-child interaction, child behaviour and child development have the potential to reduce child injuries. Educational anticipatory guidance has been recommended, but no such programmes currently exist. Aims/Objectives/Purpose: We aimed to develop a parenting programme that provided injury prevention education tailored to the stages of child development, for parents of preschool children who had sustained a medically attended injury in the last year. Methods: Working with two voluntary sector organisations; Parenting UK and the Whoops! Child Safety Project, we developed a programme based on evidence-based components of existing parenting programmes where available and appropriate. The programme was evaluated against a validated parenting programme evaluation tool, against injury prevention criteria, and deliverability assessed through a feasibility cluster randomised trial. Results/Outcome: An 8-week, group-based programme was developed where recommended parenting practices were illustrated with child injury risk scenarios, and included first aid advice as well as safety promotion. Four courses were delivered and feedback from parents and providers collected. The course was broadly welcomed by practitioners and acceptable to some parents. Recommendations for future use and development were given. Significance/Contribution to the Field: The programme has the potential to be tested in a multicentre randomised controlled trial to determine effectiveness and cost-effectiveness in reducing injury occurrence. The potential stigma felt by parents of children who have been injured should not be underestimated and provides a major challenge for recruitment to such programmes.